Successful Surgical Treatment of a Spontaneous Rupture of the Esophagus Diagnosed Two Days after Onset - Hiroyuki Ando; Yoshinori Shitara; Kei Hagiwara; Keigo Hara; Yasushi Mogami; Tsutomu Kobayashi; Toshiki Yajima; Masachika Tani; Nobuhiro Morinaga; Masatoshi Ishizaki; Hiroyuki Kuwano (Case Reports in Gastroenterology, 2012)
Esophageal perforation is a relatively uncommon disease with a high rate of mortality and morbidity. Delay in the diagnosis and treatment occurs in more than 50% of cases, leading to a mortality rate of 40–60%. Primary repair is generally considered the gold standard for patients who present within the first 24 h following perforation of the esophagus. In this paper, we present a case of successful surgical treatment of spontaneous rupture of the esophagus that was diagnosed 2 days after onset. The patient was a 42-year-old man admitted to internal medicine with a diagnosis of pleuritis and complaining of chest and back pain. The next day, computed tomography revealed left-sided pleural effusion and mediastinal emphysema. An esophagogram revealed extravasation of the contrast medium from the lower left esophagus to the mediastinal cavity. These results confirmed a rupture of the esophagus, and an emergency left thoracotomy was performed. The perforation was repaired with a single-layered closure and was covered with elevated great omentum obtained by laparotomy. The patient was discharged 23 days after the first surgery. In conclusion, primary repair surgery must be selected as the best treatment beyond 24 h if the patient’s general state was stable and there was no evidence of clinical sepsis.